ANALISIS TITIK PULANG POKOK USAHA KERIPIK PISANG GULA AREN PADA INDUSTRI “FLAMBOYAN” DI KELURAHAN PANAU KECAMATAN TAWAELI KOTA PALU - Nitha, Vella; Damayanti, Lien (AGROTEKBIS, 2018)
This research aims to know the revenue obtained in the business of banana chips Palm sugar industry Flamboyant period of 3 months in order this businesses  reaches breakeven point, or in other words the venture suffered no loss or gain profit. The research was carried out on the industry's "flamboyant" TawaeliSubdistrict of the city of palu. Respondents were drawn from this research consists of 1 leader and 2 employees. The analysis used in the study is the analysis of the break-even Point. The results of the analysis of the breakeven industry "flamboyant" in July is reached at the time of the sales volume reached 391 packaging/150 gr with revenue of Rp.3,910,000,-and for the month of August reached breakeven at the time the sales volume reached 367 packaging/150 gr with revenue of Rp.3,670,000.-. In September reached breakeven at the time the sales volume reached 366packaging/150 gr with revenue of Rp.3,660,000 ,-. Key words: Cost, Breakeven, Revenue, Reception.